2010
DOI: 10.1111/j.1365-294x.2010.04653.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal increase in mtDNA diversity in a declining population

Abstract: In small and declining populations levels of genetic variability are expected to be reduced due to effects of inbreeding and random genetic drift. As a result, both individual fitness and populations' adaptability can be compromised, and the probability of extinction increased. Therefore, maintenance of genetic variability is a crucial goal in conservation biology. Here we show that although the level of genetic variability in mtDNA of the endangered Fennoscandian lesser white-fronted goose Anser erythropus po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
5
14
0
Order By: Relevance
“…This amount of sex-biased gene-flow is much larger 472 than what we observed by performing the same calculations for the Canada goose (up to times greater). Evidence of the sex-biased dispersal has been found also in the lesser-white 474 fronted goose (Ruokonen et al 2010) In this study we found that over half of the Finnish bean goose bag consists of the declining taiga 516 bean geese and that the tundra bean goose portion of the bag comes mainly from south-eastern 517…”
Section: Composition Of the Hunting Bag 386supporting
confidence: 51%
“…This amount of sex-biased gene-flow is much larger 472 than what we observed by performing the same calculations for the Canada goose (up to times greater). Evidence of the sex-biased dispersal has been found also in the lesser-white 474 fronted goose (Ruokonen et al 2010) In this study we found that over half of the Finnish bean goose bag consists of the declining taiga 516 bean geese and that the tundra bean goose portion of the bag comes mainly from south-eastern 517…”
Section: Composition Of the Hunting Bag 386supporting
confidence: 51%
“…comm.). A similar finding of sex-biased genetic diversity was documented by Ruokonen et al (2010) for the Fennoscandian lesser white-fronted goose (Anser erythropus) where haplotypic richness increased dramatically over time as a result of increased immigration by males. Because mtDNA is maternally transmitted and female waterfowl species may return to their natal site for subsequent breeding, dispersing males may offer an index of genetic diversity on a larger scale and are thus useful for population genetic surveys in species with sex-biased movement patterns.…”
Section: Resultssupporting
confidence: 57%
“…Thus, the observed latitudinal cline in the number of migrants suggests that larval dispersal is predominantly northwards, reflecting the prevailing wind regimes and tidal currents in the area (Cáceres, Valle-Levinson & Atkinson, 2003;Bustos, Landaeta & Balbotin, 2008). High gene flow can help prevent the loss of genetic diversity among diadromous G. maculatus in the short term (Ruokonen et al, 2010). However, given the importance that dispersal has for the evolutionary history of this species (Waters et al, 2000), a disruption of connectivity could have long-term fitness consequences.…”
Section: Discussionmentioning
confidence: 99%